The Core Principles for Islamic Finance Regulations and Assessment Methodology. (Policy Papers; Policy Paper, 2018)
This paper provides a proposal to incorporate the Core Principles for Islamic Finance Regulation (Banking Sector) (CPIFR) issued by the Islamic Financial Services Board (IFSB), as part of the standards used in assessing the banking regulatory and supervisory regimes of relevant member jurisdictions under the Financial Sector Assessment Program (FSAP) and the Reports on Observance of Standards and Codes (ROSCs). The CPIFR largely reflects the order of the Basel Core Principles on Effective Banking Supervision (BCP), with five additional principles that are specific to Islamic banking operations. Thus, for countries that have systemically significant Islamic banking sector, the assessment of the banking regulation and supervision regime of the jurisdiction would be against the CPIFR (for fully Islamic banking systems) or BCP and the five additional core principles under the CPIFR (for dual banking systems). The Fund staff is seeking the endorsement of the Executive Board on this proposal.